Features of drying process of artificially cultivated mushrooms - Bobel (Zinchenko), Inna; Terletska, Vita (My University, 2013)
This paper describes the analysis of drying and taste additives influence on the changes of chemical composition and quality parameters of Pleurotus Ostreatus and Agaricus bisporus mushrooms and their ready-to-cook mushroom foods. We tested and scientifically motivated the impact of drying on the protein substances changes and carbohydrates changes (contents of glycogen, dextrines, reducing substances, cellulose) of ready-to-cook mushroom foods. У цій статті описано аналіз впливу сушіння та смакових добавок на зміни хімічного складу та показників якості грибів Pleurotus Ostreatus та Agaricus bisporus, а також готових до приготування грибних продуктів з них. Ми перевірили та науково обґрунтували вплив сушіння на зміни білкових речовин та вуглеводів (вміст глікогену, декстринів, редукуючих речовин, целюлози) готових до приготування грибних продуктів.
Keywords: pleurotus ostreatus; agaricus bisporus; mushroom products; глива звичайна; печериця двоспорова; грибні продукти; кафедра технології хлібопекарських і кондитерських виробів